KEPENTINGAN BRAZIL MENOLAK CREDENTIAL LETTER INDONESIA DALAM KASUS EKSEKUSI MATI SINDIKAT NARKOBA INTERNASIONAL TAHUN 2015 - Haiga, Juli; Rani, Faisal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study analyzes the interests of Brazil Refuses Indonesia Credential Letter Dead In Case Execution Drug Syndicate International Year 2015. The rate of drug crimes in Indonesia have continued to rise, followed by the type of drug and the modus operandi vary continuously changing. Indonesia has become the target of an international drug syndicate. The administration of President Jokowi matiter establish penalties against drug cases. The policy raises the pros and cons, especially in the country of origin of the convict. Brazil has sentenced two citizens to the dictates of the maliter.Drug syndicate case involving the Brazilian Marco Archer Cardoso Moreira was caught 13,4 kg of cocaine August 2003 in Banten and RedirgoGuarte smuggle cocaine hidden in her surfboard weighing 19 kilograms July 2004 in Banten.The theory put forward is about the interests of the country. This research topic is the existence of other instruments used to achieve political purposes that utilizes a special report from Amnesty International. Another theory used in this study is Diplomacy. Brazil made a mistake by refusing Credential letter Indonesia with Indonesia cornerstone of the death penalty against citizens in drug cases. It is the theory of diplomacy is a violation of the code of conduct diplomacy.Keywords: Brazil, Credential letter, Ethics Diplomacy, Indonesia, National Interest